2018
DOI: 10.1007/s00262-018-2247-4
|View full text |Cite
|
Sign up to set email alerts
|

Sustained efficacy of adjuvant immunotherapy with cytokine-induced killer cells for hepatocellular carcinoma: an extended 5-year follow-up

Abstract: Our earlier multicenter randomized controlled trial showed that adjuvant immunotherapy with cytokine-induced killer (CIK) cells resulted in longer recurrence-free survival (RFS) and overall survival (OS) as well in patients who received curative treatment for hepatocellular carcinoma (HCC). In the present study, we determined if the efficacy of CIK cell therapy continued after end of repeated CIK cell injections. We performed a follow-up study of our preceding trial. We included 226 patients: 114 patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…To prepare CIK cells, peripheral blood precursors from healthy donors were activated with anti-CD3 and anti-CD28 antibodies, and maintained in IL-2 supplemented T-cell culture medium for 10-15 days. 24 After subjecting NK-92MI and CIK cells to Because most leukemia and lymphoma cells require a close relationship with the bone marrow microenvironment for their survival and disease progression. 37,38 We reasoned that NK cells may not be sufficiently trafficking to bone marrow to attack B lymphoma where they reside in situ.…”
Section: Engineering High-affinity Ligands On Nk-92mi and Cik Cells Fmentioning
confidence: 99%
See 2 more Smart Citations
“…To prepare CIK cells, peripheral blood precursors from healthy donors were activated with anti-CD3 and anti-CD28 antibodies, and maintained in IL-2 supplemented T-cell culture medium for 10-15 days. 24 After subjecting NK-92MI and CIK cells to Because most leukemia and lymphoma cells require a close relationship with the bone marrow microenvironment for their survival and disease progression. 37,38 We reasoned that NK cells may not be sufficiently trafficking to bone marrow to attack B lymphoma where they reside in situ.…”
Section: Engineering High-affinity Ligands On Nk-92mi and Cik Cells Fmentioning
confidence: 99%
“…20 Cytokine-Induced Killer (CIK) cells, generated by ex vivo incubation of human peripheral blood mononuclear cells (PBMC) or cord blood mononuclear cells, feature a mixed T-and natural killer (NK) cell-like phenotype. [21][22][23][24] Like NK-92MI cells, the intrinsic tumor killing ability of CIK is mainly mediated by the NKG2D receptor that recognizes, in MHC-independent manner, stress-inducible targets. 24 We hypothesize that by using high-affinity and specific CD22 ligands to functionalize NK-92MI and CIK cells, specific targeting and killing of tumor cells with CD22 over-expression can be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIK cell adjuvant therapy also reduces the recurrence in HCC patients undergoing curative treatment [117] . Lee et al [118] found that the efficacy of CIK cells in patients with HCC lasted over 5 years. Chang et al [119] reported that the high number of PD-1 + tumor infiltrating lymphocytes could predict the response and clinical benefits of CIK cell adjuvant immunotherapy in HCC patients.…”
Section: Cytokine-induced Killer Cell Adjuvant Therapymentioning
confidence: 99%
“…22 In an extended 5-year follow-up study, patients who received an adjuvant CIK cell immunotherapy for HCC showed significant improvement in recurrence-free and OS that lasted for over 5 years without additional booster treatments. 23 A meta-analysis of eight randomized clinical trials and six prospective studies revealed that CIK treatment increased the rate of patient survival, but did not prolong progression-free survival. 24…”
Section: Cik Cellsmentioning
confidence: 99%